Enhancing the Effectiveness of the Universal Basic Education Counterpart Funding Policy in Nigeria: Challenges, Prospects, and Strategic Reforms - Okafor Ikechukwu Maduka; Folasade Serifat AKINOLA-OJEDOKUN (Researchparks Publishing, 2026)
The Universal Basic Education (UBE) programme was introduced in Nigeria in 1999 as a strategic intervention aimed at providing free, compulsory, and universal basic education for all school-age children. To facilitate the achievement of its objectives, the Federal Government established a counterpart funding policy through the Universal Basic Education Commission (UBEC), requiring state governments to contribute matching funds before accessing federal intervention grants. The policy was designed to promote shared responsibility, increase educational financing, improve accountability, and accelerate the development of basic education infrastructure and services across the country. Despite the significant resources committed to the programme, many states have faced difficulties in accessing and utilizing counterpart funds due to financial constraints, weak institutional capacity, poor accountability mechanisms, political interference, and inadequate commitment to educational development. Consequently, substantial amounts of intervention funds have remained unaccessed while educational challenges such as inadequate infrastructure, teacher shortages, and high numbers of out-of-school children persist. This paper reviews the UBE counterpart funding policy in Nigeria with a view to examining its objectives, implementation challenges, and possible strategies for improving its effectiveness. The study adopts a review methodology relying on existing literature, policy documents, government reports, and empirical studies. Findings indicate that while the counterpart funding policy has contributed to improvements in educational infrastructure and access, several structural and administrative challenges continue to hinder its optimal performance. The paper recommends the adoption of a differentiated counterpart funding formula, strengthening of monitoring and accountability systems, enhanced capacity building for educational administrators, performance-based funding mechanisms, and increased stakeholder participation in educational financing.